Environmental Awareness, Ecotourism Awareness and Ecotourism Perception of Tourist Guides - Uzulmez, Meral; Ercan Istin, Aysen; Barakazi, Ebru (Mdpi, 2023)
The tourism sector operates intensively in the ecological environment with tourist guides, who are accepted as the guiding recreation leader within the scope of outdoor activities. From this point of view, it is aimed to determine the ecotourism perception and environmental awareness of tourist guides by determining the criteria affecting the perception of ecotourism. Within the scope of the research, 336 answers were obtained by asking questions to the professional tourist guides who are actively operating throughout Turkey. In the light of the research data, mostly positive relations were determined by the correlation analyses for the environmental awareness dimensions. In the regression analyses conducted to explain the relationship between the perception of ecotourism and the awareness of ecotourism, it was concluded that the effects of the awareness and ecotourism knowledge dimensions on the economic contribution of ecotourism were significant. This research, aims to contribute to the relevant scientific field via the evaluation of environmental awareness and ecotourism awareness in a sustainable context. In the context of environmental sustainability, the research tries to eliminate the lack of knowledge in the relevant literature by revealing the ecotourism awareness and approaches of tourist guides. In addition, it is recommended to conduct more research on the subject by drawing attention to the relationship between the ecological environment and tourism sustainability.
Keywords: ecotourism; environmental awareness; perception; tourist guide; sustainability